Bilinear elastic property of the periodontal ligament for simulation using a finite element mandible model - Borák, Libor; Florian, Zdenek; Bartáková, Sonia; Prachár, Patrik; Murakami, Natsuko; Ona, Masahiro; Igarashi, Yoshimasa; Wakabayashi, Noriyuki (Dental materials journal, 2011)
This study aimed to introduce a procedure for determining the bilinear elastic moduli (E1 and E2) of the periodontal ligament for a mathematical tooth model to analyse stress in the mandible. The bone and tooth morphology were scanned from a dry skull and an extracted intact tooth, respectively, and reconstructed in a three-dimensional finite element model. The model showed good agreement with previously reported in vivo premolar movement when an E1 for the first phase tooth movement of 0.05 MPa and an E2 for the second phase of 8.0 MPa with ε(12) of 0.075 were adopted. The mandible model analysis indicated that a remarkably high maximum compressive stress in the cervical cortical bone and the tensile stress in areas of masticatory muscle attachment were found. Future stress analyses using a jaw model may follow the process of determination of bilinear moduli to enhance accurate simulation with less calculation time.
Keywords: Imaging, Three-Dimensional; Finite Element Analysis; Odontometry; Mandible; Bicuspid; Humans; periodontální vaz; premolár; Tooth Socket; hrot zubního kořene; Computer Simulation; musculus pterygoideus; Models, Biological; modul pružnosti; Tooth Root; lidé; zubní korunka (anatomie); síla skusu; počítačové zpracování obrazu; Image Processing, Computer-Assisted; Tooth Crown; Tooth Apex; Elastic Modulus; Stress, Mechanical; pohyb; zubní lůžko; musculus masseter; počítačová simulace; musculus temporalis; Periodontal Ligament; zubní kořen; biologické modely; Movement; zobrazování trojrozměrné; Bite Force; mandibula; Temporal Muscle; biomechanika; Pterygoid Muscles; Biomechanical Phenomena; Masseter Muscle; odontometrie; Alveolar Process; processus alveolaris; analýza metodou konečných prvků; mechanický stres